M Analisis Manajemen Strategik Kepala MTs Ishlahul Muslimin Senteluk Lombok Barat Perspektif SWOT - Abdul Hanan (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
This research is a qualitative descriptive field research which examines the Principal’s Strategic Management Based on SWOT Analysis at the Islamic Junior High School ‘Ishlahul Muslimin’ in Senteluk, West Lombok. Data is collected through through observations, interviews, and documentation which is then analysed through data reduction, data display, and verification. The reseach subjects are the chairman of the school committee, the headmaster, the vice principals (curriculu affai; student affairs; public relations, facilities and infrastructure affairs) and teachers. This research aims to (1) describe the procedure of the MTs Ishlahul Muslimin’s Principal’s Strategic Management, (2) identify the implementation of SWOT analysis at MTs Ishlahul Muslimin Senteluk Lombok Barat, and (3) identify the internal and external factors related to MTs Ishlahul Muslimin’s program implementation. The results of this study indicate that : (a) the principal’s Strategic Management is considered to be innovative and flexible, (b) the implementation of SWOT analysis at MTs Ishlahul Muslimin Senteluk Lombok Barat has three phases: strategy formulation, strategy implementation, and strategy evaluation, and (c) the internal factors related to the program implementation at MTs Ishlahul Muslimin are learner analysis, educators analysis and curriculum analysis. The external factors include the analysis of the social environment of the community and the analysis of the role of government.